Uma casa, uma sala, um ponto, uma linha e um conto: narrativas (auto)biográficas desenhadas entre uma professora artista e crianças de 6º anos de uma escola pública em Caucaia-CE - Torres, Klaudiana Viana (2023)
This dissertation addresses the experience of an artist teacher in training with her 6th year students at Public School Flávio Portela Marcílio, in the city of Caucaia – Ceará, Brazil, during the Covid-19 pandemic in remote mode learning in the Arts discipline. It aims to build an (auto)biographical dialogue between teacher and students through drawing (Mèredieu, 2004; Derdyk, 1989) and identify the elements that give them social, cultural and personal identity for the construction of an autobiographical tale. In the methodological aspect, this is a qualitative research (Deslandes, 1992; Minayo, 2001) characterized as an (auto)biographical research (Delory-Momberger, 2012, Goldberg, 2019, 2021; Passeggi, 2008, 2014) that proposes dialogue between the production of autobiographical narratives drawn between the teacher/artist and the students, composing a corpus based on the drawings of eight most frequent and participatory students in classes, where data production took place through logbooks, audios, photographs and mainly drawings. To achieve our general objective and insertion as a mediator on equal terms between teacher and students and enhance the meeting in the virtual space of the classroom, fostering a relationship of self-knowledge and exchange of experiences, the (auto)biographical narrative designed from the childhood teacher, until the present day, who was the subject of dialogue and interaction with the class. We investigate, through drawings produced by students, the elements that express and constitute their social, cultural and historical identities. In the (auto)biographical dialogue constructed between teacher and students, the existence of drawings that showed ethnic diversity and the predominance of the Catholic religion was relevant. It was also possible to observe the precarious situation, where, in most houses, more than one family lives and that despite the economic needs and pain resulting from the Covid-19 pandemic, what most marked the drawings was the happiness expressed. Inspired by these drawings, the teacher created a story that tells the story of each student, reinforcing the time and space where this happens, emphasizing their identity. As a result, we observed the importance of this transgenerational encounter between teacher and students, identifying the elements that exist in common and those that differ in the child of the teacher's past and in the student who is a child now. Despite the guidance given to children, speech was often silenced due to the environment full of adults, but what was silenced in speech was expressed through drawing, giving this language its expressive importance and the need to value and encourage expression drawing in elementary school 2, at which point the vast majority of children stop drawing. It is also concluded that despite the difficulties in holding remote meetings, the art classes were happy meetings as the autobiographical dimension created bonds of affection between teacher and students, a precious space for dialogue and exchange of subjective experiences with drawing as a formative element. and connecting communication and self-construction, giving meaning to what is experienced even in such difficult times.